UJI AKTIVITAS GEL LENDIR BEKICOT (ACHATINA FULICA) SEBAGAI PENYEMBUHAN LUKA SAYAT - Shoviantari, Fenita; Fajriyah, Shofiatul; Agustin, Ela; Khairani, Shafia (Jurnal Ilmiah As-Syifaa, 2021)
Snail mucus (Achatina fulica) has a high protein content, which includes beta agglutinin, achasin protein, acharan sulfate, and glycoconjugate. The objectives of this study was to determine differences in physical evaluation of the quality of the gel preparation against snail mucus concentration and to determine the efficacy of snail mucus gel as a wound healing. This study used an experimental research method with a sample of 4 male rats (Rattus novergicus) which were divided into 6 groups in each. The results showed that there was no effect of the physical quality of snail slime gel (Achatina fulica) on the concentration of snail slime formulated. It has been proven in the Kruskall wallis statistical test with the Sig. > 0.05. The results of the wound healing activity test showed an average value of K (+) 49.61%, K (-) 17.48%, P1 48.23%, P2 43.63%, P3 43.43%, and P4 23, 97. Values that indicate differences in K (-) and P4 are evidenced in the Post Hoc LSD test with Sig. <0.05. It can be concluded that the concentration of snail mucus does not affect the physical quality of snail mucus gel preparations and snail mucus gel with snail mucus concentration of 10% is effective in the process of wound healing.